Physical science content knowledge of first-year preservice science teacher trainees at colleges of education in South Africa - Howie, Sarah J (My University, 2014)
First year science teacher trainees' physical science content knowledge was tested in a survey conducted at six historically black Colleges of Education in South Africa. The science achievement tests included questions on oxidation-reduction/ electrochemical cells; velocity/ displacement; periodic table and electrostatics. This exploratory study revealed that the students had a very low content knowledge of all four science topics. Students had difficulty answering open-ended questions and a high percentage of students were unable to answer questions requiring knowledge of basic scientific facts and principles. Background questionnaires were also administered to the students. More than 75% of the students tested did not foresee teaching as a career. Furthermore, students’ confidence about their content knowledge and positive attitudes towards science did not correlate with their performance in the achievement test. The study proposes a revised strategy on recruitment and the selection of teacher trainees for physical science at the Colleges of Education.
Thesis (M.Ed.)--University of the Witwatersrand, Faculty of Education, 1999